Effect of electric poling on structural, magnetic and ferroelectric properties of 0.8PbFe0.5Nb0.5O3-0.2BiFeO3 multiferroic solid solution. Issue 10 (July 2019) - Dadami, Sunanda T.; Rayaprol, Sudhindra; Sathe, Vasant; Angadi, Basavaraj
Abstract: The effect of electric poling on structure, magnetic and ferroelectric properties of 0.8PbFe0.5 Nb0.5 O3 -0.2BiFeO3 (0.8PFN-0.2BFO) multiferroic was studied through XRD, Raman, magnetic and ferroelectric measurements. Single step solid state reaction method was adopted to synthesize single phase 0.8PFN-0.2BFO multiferroic at lower calcination and sintering temperature. Room temperature (RT) XRD pattern before and after poling confirmed the monoclinic structure with Cm space group. Rietveld refined XRD for poled and unpoled sample shows the influence of electric poling on Fe-O1, Fe-O2, Nb-O and Bi-O modes. There is a small variation in the lattice parameters after electric poling. The structural properties were also studied in detail for the poled and unpoled 0.8PFN-0.2BFO using Raman spectroscopy. Raman measurements were carried out over a wide range of temperature (250–550 K) for both poled and unpoled samples. At RT unpoled 0.8PFN-0.2BFO multiferroic exhibit 8 active modes at 211, 263, 440, 484, 571, 706, 785 and 1120 cm -1 in the frequency range 100–1200 cm -1 . The Raman peaks exhibits significant changes in intensity as well as shape of the spectra at the characteristic temperature T C (470 K) and T N (310 K). Poled Raman spectra show major changes in the Fe/Nb-O modes intensities around TN and are due to dynamic nature of spin phonon coupling. Changes observed in the temperature dependent magnetic measurements i.e. ZFC/FC and M − H loop evidence the existence of converse magneto-electric coupling (CME) and this is due to the poling effects on Fe-O, Nb-O active modes. Due to rotation of the oxygen octahedral the electric field induced strain will originate in the system. P-E loops after poling show an increase in remnant polarisation and coercive field due to an improvement in domain ordering. The potential tunability of magnetisation with electric poling is an ideal tool for realisation of application in practical devices.